Analysis of the CD8+ IL-10+ T cell response elicited by vaccination with the oncogenic tumor-self protein D52 - C. Riccay Elizondo; Jennifer D. Bright; Jennifer A. Byrne; Robert K. Bright (Taylor & Francis Group, 2020)
Development of cancer vaccines targeting tumor self-antigens is complex and challenging due to the difficulty of overcoming immune tolerance to self-proteins. Vaccination against tumor self-protein D52 (D52) has been successful, although complete protection appears impaired by immune regulation. Our previous studies suggest that vaccine elicited CD8 + T cells producing interleukin 10 (IL-10) may have a negative impact on tumor protection. Understanding the role CD8+ IL-10 + T cells play in the immune response following vaccination with D52 could result in a more potent vaccine. To address this, we vaccinated IL-10 deficient mice with the murine orthologue of D52; vaccination of wild type (wt) C57BL/6J served as a control for comparison. In separate experiments, D52 vaccinated wt mice were administered IL-10R-specific mAb to neutralize IL-10 function. Interestingly, we observed similar protection against primary tumor challenge in the experimental groups compared to the controls. However, individual IL-10 deficient mice that rejected the primary tumor challenge were re-challenged 140 days post-primary challenge to access vaccine durability and immunologic memory against tumor recurrence. Mice deficient in IL-10 demonstrated a memory response in which 100% of the mice were protected from secondary tumor challenge, while wt mice had diminished recall response (25%) against tumor recurrence. These results with analysis of vaccine-elicited CD8 + T cells for tumor-specific killing and regulatory cell marker expression, add further support to our premise that CD8+ IL-10 + T cells elicited by D52 tumor-self protein vaccine contribute to the suppression of a memory CTL responses and durable tumor immunity.